Speech technologies for blind and low vision persons. - Freitas D; Kouroupetroglou G (Technology & Disability, 2008)
In this work a review of speech technologies and their applications that provide or augment access to the printed or electronic information, the daily or social activities, as well as the private or public facilities for blind or low vision persons is presented. Speech technologies are currently considered to be essential for providing general purpose interfacing besides providing accessibility for the people who are visually impaired. Speech-enabled devices, reading machines, accessible computers, software applications, World Wide Web (WWW) content and structured environments constitute the main areas addressed throughout this paper with reference to the background technologies, architectures, formats, on-going research activities and projects. In the state-of-the art of the accessibility field, the speech communication channel is considered by the authors as one of the most important modality to benefit the blind and low vision persons.